Mineral composition of weed vegetation in wheat crop in Skopje agricultural area - Kratovalieva, Suzana; Cvetanovska, Lenka; Mulev, Milto; Dimeska, Gordana (Macedonian Journal of Ecology and Environment, 2003)
In Skopje agricultural area, v. Ljubanci in soft wheat (Triticum aestivum L.) crop the mineral composition was studied at base culture and weed species that characterised with a high abundance. Content of apsorbed and translocated manganese, iron (minor-), calcium, magnesium, potassium and phosphorous (major elements) in aboveground plant part is established according AAS. Analyse samples are taken in the phase of flowering, milky and waxy maturity of culture development. Wheat culture is supplied in satisfied framework with the investigated bioelements except low potassium concentration recorded in aboveground phytomass. At culture a potassium content is low and it is evaluated 20775 ppm-flowering, 22384 ppm-milky maturity as well as 16786 ppm-waxy maturity against total in weed phytomass 76744 ppm-flowering, 22384 ppm-milky maturity and 79757 ppm-waxy maturity. A high content of defficitary bioelements at weed component is presented a limitary factor about culture satisfied supplying and guarantied high yield as initiation in agricultural practice.